EVALUATION OF THE INFLUENCE IMMEDIATE OF LUMBOSACRAL MOBILIZATION AND MANIPULATION TECHNIQUES ON STATIC POSTURAL ACTIVITY AND PLANTAR SURFACE CONTACT IN INDIVIDUALS WITH CHRONIC LOW BACK PAIN (Fiep Bulletin - online, 2013)
Low back pain is one of the most painful disorders who affect humans, affecting about 90% of individuals at some point in their lives. Objective: Evaluating  the influence immediate of manipulation technique and articulation mobilization on the static postural activity contact surface plant in individuals with low back pain. Methodology: The purpose of this research is related to a transversal clinical assay composed of 26 participants, of both genders, being  then,  students enrolled at UNIOESTE. The study was composed by five stages: first the participants were evaluated for the inclusion and exclusion criteria. In the second phase they passed through the static baropodometric evaluation before  intervention. In the third stage were carried out kinesiological functional tests. Following of straight to intervention (fourth stage). And revaluation on the baropodometry post-intervention (fifth stage). The data was plotted in Microsoft Excel 7.0 Oficce ® and statistical analysis through the Kolmogorov-Smirnov and paired t test Student, with ?
Keywords: Low back pain; Osteopathic manipulation; Postural balance.